Diffusion of urea through membranes - Günther, Ulrike; Hartmann, Marcus; Wartewig, Siegfried; Neubert, Reinhard (Diffusion Fundamentals, 2006)
Non-invasive real time monitoring of topical drug delivery is an important subject of dermatopharmaceutical research. It has been proved that Fourier transform infrared attenuated total refection (FTIR-ATR) is a versatile technique to study drug diffusion through artificial membranes and biological systems. Urea is widely used as moisturizer or ceratolyticum in pharmaceuticals, therefore, its diffusion behaviour in biological membranes is of great interest.